Lateral Load Resistance of Laminated Veneer Lumber Sengonwooden Joints with Wooden Dowels - Palaeowati, Niken; Awaludin, Ali; Siswosukarto, Suprapto (Makara Journal of Technology, 2014)
Analytical models for wooden-doweled joints need to be developed. The objective of this research is to determine whether the strength of wooden-doweled joints can be well predicted by equations developed for steel-doweled joints. In this experiment, various connection parameters, such as dowel diameter, species of the wooden dowel, and angle of joints, are studied. The joint specimens are loaded in a quasi-static state with four replications each. A5% offset diameter method is used to determine the lateral load resistance of the tested joints, while the predictions are evaluated by equations given in Indonesian National Standard (SNI) 7973-2013 and the European Yield Model (EYM). The results show that experimental lateral resistance is greater than that of the SNI prediction and is between the EYM prediction of elastic and the plastic conditions of the wooden dowel. Lateral load resistances given by the SNI and the elastic condition EYM are around 64.53% and 78.45% of the experimental result, respectively. In contrast to steeldoweled joints, the ductility coefficient of wooden-doweled joints increases as the dowel diameter increases. This is potentially due to the axial stiffness of the wooden dowels being relatively smaller than that of the wood member. Joint failure occurs due to plastic bearing deformation in the wood member surrounding the dowel, followed by the formation of two plastic hinges in the wooden dowel.